Visual disturbances and stroke - Lubiński, Wojciech; Nowacka, Barbara; Cyryłowski, Lech (Klinika Oczna / Acta Ophthalmologica Polonica, 2022)
A large portion of the central nervous system is involved in visual function and therefore visual loss can be a residual manifestation of stroke. On the other hand, transient visual disturbances might be the first symptom of stroke development.